Learning Strategies and Applications in Learning Achievements - Deak, Victor; Santoso, Rivosa (IJOSMAS, 2021)
Strategy is an overall approach related to the implementation of ideas, planning, and execution of activity within a certain period. Strategy is an approach to achieve victory. In the world of education, strategy is a plan on ways to utilize and use existing potential and facilities to increase the effectiveness and efficiency of learning. The selection and determination of the right strategy determine the achievement of learning objectives and national education goals. The teaching and learning process is not an easy job, because the future of students, the future of the nation and state is borne by educators, without good and professional teachers there are no good and professional students. been a good student, and a bad teacher because he was once a bad student. A fairly high standard is attached to the teacher. A teacher must dedicate himself and his life to education. A successful educator can transform his knowledge in the right way and can bring his students to achieve their goals. In this research, the writer uses descriptive qualitative research. The author describes the importance of selection and strategy in the teaching and learning process by using library sources. This research provides a new contribution in the selection of learning strategies so that learning objectives or achievements can be realized.